2021
DOI: 10.3390/healthcare9101291
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Narrative Learning to Bridge the Generation Gap in Humanistic Care Nursing Education

Abstract: Background: The development of nursing students’ ability to practice humanistic care is extremely important. Methods: This study explored students’ learning experience when providing humanistic care for older adults with chronic diseases while employing intergenerational narrative learning. An exploratory descriptive qualitative study design was adopted. Results: We analyzed evaluations from 35 students who completed the course, in which intergenerational narrative learning was employed. Evaluations contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…[2] Nursing students' humanistic care ability directly determines their ability to work in the nursing profession in the future. [3] Therefore, how to cultivate and improve the humanistic care ability of nursing students is the primary task in nursing education. At present, there are many researches on the humanistic care ability of nursing students, but fewer on the mediating effect of humanistic care ability.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Nursing students' humanistic care ability directly determines their ability to work in the nursing profession in the future. [3] Therefore, how to cultivate and improve the humanistic care ability of nursing students is the primary task in nursing education. At present, there are many researches on the humanistic care ability of nursing students, but fewer on the mediating effect of humanistic care ability.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of valid tools to evaluate the quality of humanistic care adds to the challenge of motivating nurses to provide humanistic care. Systematic reforms are needed to make clinical settings more humanistic care-friendly for nurses and nursing students [9,13].…”
Section: Discussionmentioning
confidence: 99%
“…It is of utmost importance to understand students' perspectives so that we can develop a more applied student-centered nursing education program that can better prepare our students to value humanistic spirits and provide humanistic care in their work. The current body of literature focused on faculty members' experiences of developing or adapting courses or teaching methods to facilitate humanistic care education and the effects of the education on students' competencies such as "soft skills", empathy, communicative skills, and so forth [1,4,10,11,13]. However, there is a paucity of literature exploring students' experiences and perceptions of learning and applying humanistic care from school to clinical settings (practicum) in a country with the largest older population and lower health care resources.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified that intergenerational narrative inquiry can effectively improve the quality of humanistic care in nursing students [37]. Nursing students can change patients' perspectives on chronic diseases by understanding life stories of the elderly, inspiring students with a humanistic attitude, and deepening students' self-awareness.…”
Section: Teaching Strategies In Humanities Educationmentioning
confidence: 99%
“…Nursing students can change patients' perspectives on chronic diseases by understanding life stories of the elderly, inspiring students with a humanistic attitude, and deepening students' self-awareness. Through empathetic understanding, communication between generations can improve, which generate more positive attitudes toward the elderly from the students [37]. It helps nursing students to understand patients and illuminate the intricacy of specific phenomena and the paradigms that shape peoples' experiences [38].…”
Section: Teaching Strategies In Humanities Educationmentioning
confidence: 99%